Rationale and design of the ELEANOR trial early aortic valve surgery versus watchful waiting strategy in severe asymptomatic aortic regurgitation, ACRONYM: ELEANOR - Kočková, Radka; Vojáček, Jan; Bedáňová, Helena; Fila, Petr; Skalský, Ivo; Žáková, Daniela; Klán, Michal; Míková, Barbora; Mědílek, Karel; Tuna, Martin; Fialová, Monika; Dvořáková, Radka; et al. (Heliyon, 2024)
BACKGROUND: The optimal treatment of patients with severe symptomatic aortic regurgitation (AR) is state-of-the-art surgery. Asymptomatic patients with advanced left ventricular (LV) dilatation and/or impaired ejection fraction should undergo surgical treatment, but there is no guidelines consensus on cut-off values for this recommendation. Multimodality imaging has brought new tools for the accurate selection of asymptomatic patients at risk of early clinical deterioration, however, prospective and randomized data are pending. Cardiac magnetic resonance (CMR)-derived AR quantification along with LV remodeling assessment appears to be the most accurate tool for a selection of such patients at risk. TRIAL DESIGN: The objective of our prospective and multicenter study is to determine whether patients at risk of early clinical deterioration as per CMR assessment will benefit from early surgical treatment. The study is designed as a superiority trial to demonstrate that early surgical treatment is safe and more effective than the standard treatment. A total of 217 asymptomatic patients with severe AR, but without current guidelines-based surgical indication, will be enrolled across all centers. We expect 24 % of patients identified as high clinical risk and therefore eligible for 1:1 randomization to early surgical treatment within 3 months or a watchful waiting strategy. Follow-up will be annual. We expect a complete restoration of LV size and function along with improved quality of life and physical performance in a short-term follow-up of 12 months. The primary endpoint will be a composite safety and efficacy with all criteria mandatory: 15 % or larger reduction of baseline CMR-derived LV end-diastolic volume index, LV ejection fraction >50 %, and no major adverse cardiovascular events. The annual follow-up will continue for a minimum of 4 years until the required number of endpoints is achieved to show a statistically significant difference in cardiovascular morbidity and mortality in early surgically treated patients. CONCLUSION: The ELEANOR trial is the first multicenter randomized controlled study to compare early surgical treatment with a watchful waiting strategy in asymptomatic patients with chronic severe AR at high risk of early clinical deterioration as per CMR assessment but without guidelines-based indications for surgical treatment.